Optimizing Village Economic Potential Through Fried Onion Production and Packaging Training with BUMDes in Basseang Village, Pinrang: Optimalisasi Potensi Ekonomi Desa Melalui Pelatihan Produksi dan Pengemasan Bawang Goreng Bersama BUMDes di Desa Basseang, Pinrang - Jusmawandi; Muhlisah, Nurul; Suloi, Andi Fitra (Politeknik Negeri Fakfak, 2025)
Rural potential is an important asset in running the village government system. If managed properly, it will bring economic value to the village community. The fried onion production and packaging training in Basseang Village aims to increase the added value of local commodities and improve community skills in production and marketing. This program is carried out with a participatory approach involving the community, village government, and Village-Owned Enterprises (BUMDes). The results of the training showed an increase in the technical skills of participants in processing shallots into high-quality fried onions as well as an understanding of the importance of packaging and marketing strategies. In addition, this training encourages social change by increasing public awareness of local resource-based business opportunities. The main challenges faced include limited capital and production continuity. Therefore, further support from various stakeholders is needed so that this program can be sustainable and have a long-term impact on the village economy.